Introducing Islamic Banks into Conventional Banking Systems - Sole, Juan (IMF Working Papers; Working Paper ;, 2007)
Over the last decade, Islamic banking has experienced global growth rates of 10-15 percent per annum, and has been moving into an increasing number of conventional financial systems at such a rapid pace that Islamic financial institutions are present today in over 51 countries. Despite this consistent growth, many supervisory authorities and finance practitioners remain unfamiliar with the process by which Islamic banks are introduced into a conventional system. This paper attempts to shed some light in this area by describing the main phases in the process, and by flagging some of the main challenges that countries will face as Islamic banking develops alongside conventional institutions.